VD_FINDINFO Jug / 2025 / 127 vom 23. Juli 2024 - VD Tribunal cantonal (2024)
MESUREDROIT PÉNAL, PROPORTIONNALITÉ, EXPERTISE, REJET DE LA DEMANDE, MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | 56 CP, 56a CP, 59 CP, 60 CP, 63 CP, 63a CP, 63b CP